Sustainability in conservation approach: the application of 3D visual and digital tools in preparing the conservation management plan report for Masjid Negara Kuala Lumpur - Md. Sharif, Harlina; Hazumi, Hazman; Meli, Rafiq Hafizuddin (2018)
Masjid Negara (National Mosque) of Kuala Lumpur was designed to exhibit the inter-wovening of local visual culture and modern architecture during its time of conception. Constructed using reinforced concrete as the main structural framework, the mosque hails a unique architecture of an open umbrella measuring 144 feet in diameter. This concrete folded plate structure is designed to span over the main prayer hall, being supported by 16 round perimetral reinforced concrete columns, with each column rising up to 84 feet high. Apart from the main umbrella structure, the roof structure is also adorned with 95 medium-sized concrete domes and 266 smaller pyramidal ones. In recent years, water sippage has been detected in the roof structure that, if left untreated, may affect the structural rigidity of the roof. Despite various upgrading and repair works, water leakage from the roof serves as a major problem that demands for a serious assessment. The application of drone photography and 3d laser scanning was adopted in order to assess the extent of the problem. The deployment of advanced digital technologies have facilitated in the creation of heritage inventories and risk assessments thus addressing the need for sustainability. This paper discusses the materials and methods for the assessment, conservation, rehabilitation and maintenance of the sustainability of existing structures in order to produce a comprehensive conservation management plan (CMP) report for the upgrading, repair and maintenance works of Masjid Negara.